Comparison of the primary stability of a porous coated acetabular revision cup with a standard cup - Beckmann, Nicholas A.; Jäger, Sebastian; Janoszka, Maciej B.; Klotz, Matthias C. M.; Bruckner, Thomas; Bitsch, Rudi G. (The journal of arthroplasty, 2018)
Background: The number of revision hip arthroplasty procedures has been increasing substantially, with the acetabular component requiring component revision in over half of the cases. New porous implant designs attempt to improve outcomes due to improved osseointegration; however, sufficient primary stability is paramount for good osseointegration. Methods: We compared 2 revision cups of the same geometry, yet different surface properties in an in vitro scenario: a porous titanium surface and a conventional sintered-bead titanium surface. These were tested in 10 cadaveric pelvises under a physiologic cyclic partial weight-bearing scenario. Each side was randomly implanted with one of the implants. Relative motion between the bone and cup was measured using an optical measuring device. Statistical evaluation was carried out descriptively using a covariance analysis with repeated measures and a test of fixed effects, with significance determined as P < .05. Results: The conventional cup displayed an average relative motion of 28.02 μm; and the porous implant displayed an average relative motion of 33.42 μm. There was no statistically significant difference between the two with regard to the resultant relative motion (P = .2649). The bone mineral density does have a significant influence on resultant relative motion (P = .0406), with higher bone mineral density correlating with less relative motion in both implants. Conclusion: The porous implant provides similar primary stability to the conventional implant in the tested scenario; the motion of both implants relative to the bone was within safe limits for osseointegration. Bone stock must be considered when choosing implant type and postoperative care.
Available online 20 September 2017
Gesehen am 02.11.2018